2020
DOI: 10.1051/bsgf/2020018
|View full text |Cite
|
Sign up to set email alerts
|

A review of amber and copal occurrences in Africa and their paleontological significance

Abstract: The paleontological interest for fossil plant resins (amber and copal) has greatly increased in the last decades, as field studies have resulted in the discovery of various new deposits worldwide. Yet, amber-rich deposits remain particularly scarce on continents from former Gondwana. Here we review the known occurrences of copal and amber from Africa, with a state-of-the-art regarding the age dating, the putative plant sources, the fossil content, as well as the paleoenvironmental settings. The first A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 60 publications
1
19
0
Order By: Relevance
“…Schmidt et al (2010) reported the first amber outcrop from Ethiopia with inclusions and observed diverse arthropods, fungi, bacteria, and palynomorphs. Discovery of further amber-bearing Accepted Article localities in Ethiopia multiplied the number of inclusions since then, among which fossils of plants were found (Bouju & Perrichot, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Schmidt et al (2010) reported the first amber outcrop from Ethiopia with inclusions and observed diverse arthropods, fungi, bacteria, and palynomorphs. Discovery of further amber-bearing Accepted Article localities in Ethiopia multiplied the number of inclusions since then, among which fossils of plants were found (Bouju & Perrichot, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The origin of the latter piece of copal is unclear and the genus Sora is broadly distributed across East Africa as well as in Madagascar. Some other examples are mentioned by Bouju and Perrichot (2020). Conversely, in copal and Malagasy Defaunation resin, the amount of described species is much more significant involving about 100-120 species, in about 80 publications (Delclòs et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…More broadly throughout Provence, in several departments, a review of amber deposits based on many new discoveries, allows us to outline a vision of the evolution of the phenomenon of amber production from the Lower Cretaceous to the Miocene (Saint Martin et al, 2020). On the largest scale of a continent, the first synthesis of African deposits yielding copal and amber brings up a picture of a potential source of informations, until now quite unknown, especially concerning the botanical origin of resins, (Bouju and Perrichot, 2020).…”
Section: Amber: Deposits and Biodiversitymentioning
confidence: 99%